Cell-penetrating pepducins targeting the neurotensin receptor type 1 relieve pain. (May 2020) - Brouillette, Rebecca L.; Besserer-Offroy, Élie; Mona, Christine E.; Chartier, Magali; Lavenus, Sandrine; Sousbie, Marc; Belleville, Karine; Longpré, Jean-Michel; Marsault, Éric; Grandbois, Michel; Sarret, Philippe
Graphical abstract: Abstract: Pepducins are cell-penetrating, membrane-tethered lipopeptides designed to target the intracellular region of a G protein-coupled receptor (GPCR) in order to allosterically modulate the receptor's signaling output. In this proof-of-concept study, we explored the pain-relief potential of a pepducin series derived from the first intracellular loop of neurotensin receptor type 1 (NTS1), a class A GPCR that mediates many of the effects of the neurotensin (NT) tridecapeptide, including hypothermia, hypotension and analgesia. We used BRET-based biosensors to determine the pepducins' ability to engage G protein signaling pathways associated with NTS1 activation. We observed partial Gαq and Gα13 activation at a 10 μM concentration, indicating that these pepducins may act as allosteric agonists of NTS1. Additionally, we used surface plasmon resonance (SPR) as a label-free assay to monitor pepducin-induced responses in CHO-K1 cells stably expressing hNTS1. This whole-cell integrated assay enabled us to subdivide our pepducin series into three profile response groups. In order to determine the pepducins' antinociceptive potential, we then screened the series in an acute pain model (tail-flick test) by measuring tail withdrawal latencies to a thermal nociceptive stimulus, following intrathecal (i.t.) pepducin administration (275 nmol/kg). We further evaluated promising pepducins in a tonic pain model (formalin test), as well as in neuropathic ( Chronic Constriction Injury ) and inflammatory ( Complete Freund's Adjuvant ) chronic pain models. We report one pepducin, PP-001, that consistently reduced rat nociceptive behaviors, even in chronic pain paradigms. Finally, we designed a TAMRA-tagged version of PP-001 and found by confocal microscopy that the pepducin reached the rat dorsal root ganglia post i.t. injection, thus potentially modulating the activity of NTS1 at this location to produce its analgesic effect. Altogether, these results suggest that NTS1-derived pepducins may represent a promising strategy in pain-relief.